Experimental study on the translation behavior of an in-situ bubble pair in the ultrasonic field - Xiao Huang; Peng-Bo Liu; Guang-Yun Niu; Hai-Bao Hu (Ultrasonics Sonochemistry)
The dynamics of acoustic cavitation bubbles hold significant importance in ultrasonic cleaning, biomedicine, and chemistry. Utilizing an in-situ normal pressure bubble generation and observation system that was developed, this study examined the translational behavior of micrometer-scale normal pressure bubble pairs with initial radius ratio of 1:1 and 2:1 under ultrasonic field excitation. A velocity-distance curve was proposed to quantify the secondary Bjerknes forces during various interaction stages of the bubbles. The findings revealed that equal-sized bubbles underwent an acceleration phase, a deceleration phase, and a velocity jump phase during attraction in both strong and weak acoustic fields. In contrast, bubbles of unequal sizes, due to different oscillation frequencies, experienced multiple acceleration and deceleration phases, presenting asynchronous behaviors. The study further explored the effects of the initial bubble radius, shape oscillation, and volume oscillations on the attraction speed. Results showed that the velocity of the bubble’s centroid decreased with an increase in the initial radius, while intensified volume oscillations increased the secondary Bjerknes force, thereby increasing the centroid’s velocity. Moreover, strong acoustic fields were more likely to induce severe volume and shape oscillations in bubbles than weak fields. The irregular shape oscillations in twin bubbles resulted in shortened durations of acceleration and deceleration phases, reduced peak velocities of acceleration phase, and diminished acceleration during the velocity jump phase. The research provided some mechanical explanations for acoustic cavitation dynamics and its applications.